Chinas power projection - R V Phadke; PHADKE (R V) (New Delhi Manas Publications, 2005)
China's attempts to comprehensively overhaul and modernize its armed forces, and its emphasis on access to modern technology indicate the determination of the Chinese leadership to build an all-round military capability to fight well beyond its immediate periphery. Coercion, and if that fails, resorting to use of military force have been the logical and natural steps in China's strategy. This marked propensity to use force makes one take note of China's fast burgeoning military capabilities. The rapid-fire modernisation process of China's military would permit it to extend its influence and power well beyond its immediate proximity. This development has serious implications for India's security. However, to exaggerate the "Chinese threat" is counter-productive, lest it becomes a self-fulfilling prophecy. While the PRC would like the world to respect it even if out of fear or awe, it is axiomatic that India guard itself against an overestimation of the threat while assessing its potential. The book attempts to search for ways to improve an understanding of China's rapidly raising power status in international politics and its possible implications for India's security.
Keywords: Chinas Grand Strategy; Nuclear and Strategic Assets; PLA Doctrine; Implications for India's Security